The Effects of Islamic Religious Education Learning on Students’ Motivation - Murharyana, Murharyana; Al Ayyubi, Ibnu Imam; Rohmatulloh, Rifqi; Ikromi, Shoutika Nawadya (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This article aims to see whether there is a significant relationship or influence on students’ learning motivation towards Islamic religious education at MTs Arrukhshatul 'Ulum West Bandung with heterogeneous social, cultural, and cognitive factors of students using quantitative research. The research method used was a survey method with correlation analysis to see the relationship between the independent variables, namely students’ motivation, and the dependent variable, namely students’ learning outcomes, using the Problem-Based Learning (PBL) learning model. The population of this research was class IX students at MTs Arrukhshatul 'Ulum, with a sample of 30 students. The research instruments in this study used questionnaires and tests. Testing of the data analysis requirements consisted of normality tests and linearity tests with the hypotheses used, namely correlation and regression tests. From the research conducted, it was found that the data of the student’s learning motivation and students’ learning outcomes using the Problem-Based Learning (PBL) learning model is usually distributed and has a strong correlation with the strength of the coefficient with a Correlation Coefficient value of 0.952. Besides that, an interaction between learning motivation and learning outcomes of 90.5 % and the other 9.5% are influenced by external factors. Because the data is normally distributed, it is continued with a regression test, which produces data that meets the linearity criteria with the regression equation Y=32.758+0.653X.